1987
DOI: 10.1111/j.1744-7348.1987.tb01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cocksfoot mottle virus on resistant and susceptible cocksfoot cultivars grown alone or in combination with healthy or ryegrass mosaic virus‐infected Italian ryegrass

Abstract: S U M M A R YCocksfoot mottle virus (CfMV) was readily transmitted on cutting implements. However, after six harvests, only a quarter as many plants of the resistant cv. Cambria as of the susceptible cv. S.37 became infected. In addition to resistance to becoming infected, cv. Cambria also possessed some resistance once infected, and suffered less mortality than S.37. More CfMV-infected plants died when competing with healthy plants than when competing with other infected plants.Both CfMV and ryegrass mosaic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The debilitating effect of crown rust on competitive ability has been reported by Lancashire & Latch (1970), who found that infected mixed swards of perennial ryegrass and white clover became dominated by clover. Also, Trorey (1979) reported increased yields of cocksfoot when in competition with infected perennial ryegrass Virus infections, too, cause similar changes in ryegrass mixlures and in ryegrass cocksfool swards (Catherall, 1987;Cathcrall & Potter, These effecis on compctiiivc ability may be explained by the differing tillering ability and growth hiibils of cultivars Perennial ryegrass tillers freely and is usually prostrate in growth habit. Therefore, this species will be more strongly competitive on a horizontal than on a vertical plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The debilitating effect of crown rust on competitive ability has been reported by Lancashire & Latch (1970), who found that infected mixed swards of perennial ryegrass and white clover became dominated by clover. Also, Trorey (1979) reported increased yields of cocksfoot when in competition with infected perennial ryegrass Virus infections, too, cause similar changes in ryegrass mixlures and in ryegrass cocksfool swards (Catherall, 1987;Cathcrall & Potter, These effecis on compctiiivc ability may be explained by the differing tillering ability and growth hiibils of cultivars Perennial ryegrass tillers freely and is usually prostrate in growth habit. Therefore, this species will be more strongly competitive on a horizontal than on a vertical plane.…”
Section: Discussionmentioning
confidence: 99%
“…These effects reduce the competitive ability of infected plants to the advantage of other species (Lancashire & Latch, 1970). Although Catherall (1987) has shown that viruses can drastically afTect the competitive ability of infected components of mixed swards of ryegrasses, there are no detailed reports of effects of crown rust infection on mixtures of susceptible and resistant ryegrass plants.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the main approach used for each of them, the research question being addressed and their main species balance outcomes. They (Bain et al, 1998;Catherall, 1987;Catherall & Potter, 1987;Ragland et al, 1986);…”
Section: Examples and Termsmentioning
confidence: 99%
“…Thus, when in competition with a nonhost species, the susceptible, sensitive D. glomerata cultivar S.37 was suppressed to a greater extent than the partially resistant cultivar Cambria. Catherall and Potter (1987) concluded that "in mixed species swards, a virus infection in one species can greatly affect the aggressiveness of each component of the mixture. This will ultimately change the botanical composition of the sward and this in turn will affect the yield and quality of the herbage produced".…”
Section: Alter Ati On S In S Pecie S Bal An Ce In S Imul Ated Perenni...mentioning
confidence: 99%
See 1 more Smart Citation